Sorptive removal of ibuprofen from water by natural porous biochar derived from recyclable plane tree leaf waste. (April 2022) - Yang, Xu; Zhang, Xinbo; Ngo, Huu Hao; Guo, Wenshan; Huo, Jiangbo; Du, Qing; Zhang, Yufeng; Li, Chaocan; Yang, Fei
Abstract: To remove ibuprofen (IBP) in water efficiently and economically, plane tree leaf-derived biochar (P-BC) as a new adsorbent was prepared via pyrolysis at 600 °C. Textural characterizations of P-BC exhibited a porous structure and abundant hydroxyl groups. The results of FTIR and XPS indicated that -OH functional groups played a key role in the adsorption process. Batch adsorption studies were carried out at pH values of 2 to 8, adsorbent dosage of 0.1 to 2.0 g/L and initial concentrations of 500 to 5000 μg/L. Adsorption results showed that P-BC (1.0 g/L) could remove as much as 96.34% of ibuprofen (2000 μg/L) in a strong acidic environment (i.e. pH 2). The adsorption of ibuprofen by P-BC was found to be more consistent with the pseudo-second order kinetic model and Langmuir isothermal model with higher correlation coefficients of 0.999 and 0.996, respectively. Its maximum adsorption capacity was up to 10, 410 μg/g. A mechanism analysis demonstrated that the -OH functional groups on the surface of P-BC could form hydrogen bonds with IBP as donors and acceptors, respectively. It played a predominant role in removing IBP. In particular the fabricated P-BC is an effective and recyclable sorbent and its efficiency in removing ibuprofen can still reach more than 70% after five regenerations. The total production cost of P-BC is 4.05 USD / kg, which is equivalent to the treatment cost of only 0.004 USD/L wastewater. The results revealed that P-BC is an environment-friendly, low-cost and efficient adsorbent for removing IBP from water. Graphical abstract: Unlabelled Image Highlights: P-BC was prepared for the use of plane tree fallen leaves. The removal rate of IBP by P-BC was as high as 96.34% at pH 2. The maximum adsorption capacity of IBP by P-BC was 10, 410 μg/g. The hydroxyl groups on the surface of P-BC can form hydrogen bonds with IBP. The removal of IBP using P-BC was still above 70% after five adsorption cycles.